Społeczna odpowiedzialność uczelni na przykładzie Politechniki Wrocławskiej - Merta-Staszczak, Adriana; Serafin, Krzysztof; Staszczak, Bartosz (Annales. Etyka w Życiu Gospodarczym, 2020)
The research problem described in the title of the article can be formulated as a question: by what means is the idea of the University’s social responsibility implemented at the Wrocław University of Science and Technology in its operation? We are talking here about the idea of sensu largo, because universities’ social responsibility requires an even more complete theoretical conceptualization. This idea refers to the theoretically recognized, complex, constantly changing, and multi-directional and network cooperation between the University and the heterogeneous environment. The conclusions of this submission may be a stimulus for further research on the developing concept of university social responsibility. The first part of the article is based on the analysis of the literature of the subject, while the second part examines documents.